ANALISIS PERAN AKTOR DALAM FORMULASI KEBIJAKAN SEMARANG SMART CITY - Fauzi, Achmad Nur; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The city is an area that has various problems if doesn’t not managed properly. Along the time and the development of technology, Smart City comes to offer improvements to urban problems. Not only big cities in the world, Semarang as one of the big cities in Indonesia also enlivened the existence of Smart City in Indonesia. The implementation of Smart City which has high complexity must be supported by a strong regulation. Based on those needs, the Government of Semarang City formulated a Semarang Smart City policy. The problem that arises is what is the role of the actor in policy formulation of Semarang Smart City? The purpose of this study was to determine the role of actors in the Semarang Smart City policy formulation. This study uses a qualitative approach, a type of descriptive research. The results showed that there were 28 actors involved which consisted of three elements, state, private, and society. There 24 state actors, 4 private actors, and no society actor were involved. The three actors (state, private, and society) have different roles, causing a relationship between the three policy actors. The relationship between policy actors has an impact on the emergence of power and interest among policy actors and the value orientation adopted by each policy actor. Policy formulation encountered obstacles, like a lack of private and society participation which create an impression of the dominance of the role of the state. Researchers recommend the Semarang City’s Government to increase the involvement of private and society elements. In addition, a synergistic strategy between policy actors is needed so that policy formulation takes place properly.